Areca nut consumption on the number of children in couples of childbearing age - Situmorang, Cory Chorajon; Sari, Catur Anita (Universitas 'Aisyiyah Yogyakarta, 2024)
Papuans have a propensity of eating areca nuts. Chewing areca nuts was historically associated with the life of the elderly. However, areca nuts have recently gained popularity among young people in Papua. In Papua, the habit of eating betel nuts, or areca nuts, has been passed down from generation to generation for centuries. This study examines the correlation between areca nut consumption and the number of children among reproductive-age couples at the Public Health Center of East Sorong Work Region. This is a correlational study conducted using a cross-sectional design. We used a questionnaire about areca nut consumption habits and the number of children in reproductive-age couples. To test the hypothesis, bivariate analysis was utilized to determine whether there was a correlation between the independent and dependent variables using the Chi-Square test (X2). Based on the results, we found that the wife's habit of consuming areca nuts does not correlate with the number of children, while the husband's habit has a p-value <0.05. This indicates a correlation between consuming areca nuts had a significant effect on the number of children, with a p-value of 0.000 < 0.05 for the husband's habits and 0.031 < 0.05 for both habits. We believe that husbands who consume areca nuts frequently will affect the quality of sperm, which might result in impaired fertility and a decrease in the number of children.